Geoelectrical Surveys for Characterization of the Coastal Saltwater Intrusion in Metapontum Forest Reserve (Southern Italy) - Antonio Satriani; Antonio Loperte; Vito Imbrenda; Vincenzo Lapenna (International Journal of Geophysics)
A geoelectrical survey was carried out in the Metapontum Forest Reserve located along the Ionian coast of the Basilicata region (Southern Italy). In this work we used the method of two-dimensional electrical resistivity tomography for obtaining high-resolution electrical images in the investigated site. In particular, three electrical resistivity tomography, all orthogonal to the coastline, in the investigated area were carried out. To complete and integrate the geophysical data, soil and groundwater samplings, seventeen and five, respectively, were analyzed using chemical physical techniques. Geoelectrical survey, supported by laboratory analysis of soil and water samples have revealed the presence of a process of saltwater in coastal Forest Reserve of Metapontum, which have caused the decline of the existing pine forest with the consequent erosion and desertification problems. The results have disclosed the way to identify and discriminate large areas affected by intensive soil salinization and high resolution electrical images of the subsurface electrical resistivity plays a key role in delineating the saltwater intrusion front in coastal areas. Furthermore, our integrated study represents a contribution to the future programs for the protection, planning, and management of the terrestrial and marine resources in this coastal area.